RIBBONFISH FISHERY OF KAKINADA DURING 1974-1976 - Sastry, Y Appanna (Indian Journal of Fisheries, 2011)
The ribbonfi&h fishery of Kakinada during 1974-76 tesed on the landings by conMnercial trawlers showed that the annual catches varied from 371.6 to 632.4 tonnes and on an average formed’ 6.3% of the toltal fish catch. Among the six rilbbonfish species, Trichiurus lepturus dominated and accounted for 73% of the total ribbonfish landings. The seasonal abundance and species composition of all the ribbonfishes; the lecigth-weight relationships in L. gangeticus and T. russelli; and the periodicity of spawning in L. gangeticus are presented in the paper